Product Life Cycle of Yakult / Dayang Ernie Nurfarah'ain Awang Ahmad ... [et al.] - Awang Ahmad, Dayang Ernie Nurfarah'ain; Lamba, Jeffery Das; Sarkawi, Mohd Noor Idzhwan; Sarif, Fatimah (2016)
In 1930, Dr. Minoru Shirota, who was conducting research in a microbiology lab at the Medical Faculty of Kyoto University in Japan, became the first person in the world to succeed in culturing a strain of lactic acid bacteria beneficial to human health. This bacterium was named "Lactobacillus casei Shirota strain" after Dr. Shirota. At that time, Japan was not a wealthy nation, and many children lost their lives to infectious diseases and other maladies brought on by malnutrition. Deeply concerned about these conditions, Dr. Shirota was determined to focus his efforts on preventive medicine, and turned his attention to the study of microorganisms. He set about developing a stronger strain of lactic acid bacteria which would work to destroy the harmful bacteria living in the intestines, and therefore improve and maintain the health of human beings. The result of his efforts was the successful culturing of Lactobacillus casei Shirota strain. Dr. Shirota then began working together with supporters to make a delicious, yet affordable priced drink incorporating the Shirota strain so that many people could enjoy the benefits of the microorganisms. His dedication led to the development of Yakult, a cultured milk drink, which was introduced to the market in 1935. Dr. Shirota was driven by a relentless dedication to good health. His passion, creativity, and inexhaustible curiosity live on today, through the continuing progress of Yakult.